Legal Certainty: Fulfillment of Human Rights Regarding Health Within Omnibus Law Through Hospital Acreditation - Kana Purwadi; Hendra Sukarman; Dhaneswara Awindra Wijaya (Jurnal Dinamika Hukum, 2021)
The second and fourth amendment of 1945 Constitution has placed right to health as a human right. The state is obliged to fulfill health services that consists of promotive, preventive, curative and rehabilitative health services. The state is also obliged to provide a proper health service facility. The term “proper” presuppose to fulfil a particular standard. Since 8th June of 2020 to the inception of the Omnibus Law the hospital accreditation standard is based on the Health Ministry Regulation No. 12 of 2020. The inception of the Omnibus Law on 2nd November of 2020 is impacting the Law No. 44 of 2009 regarding hospital specifically associated with hospital accreditation. This research analyzes the legal certainty of human’s right to health fulfilment within Omnibus Law through the hospital accreditation settings and the urgency under the establishment of Pancasila law. The used research methodology to analyze are normative juridical by examining norms in the legislation system, conducted by researching legal materials and legal documents.Keywords: Legal certainty, omnimbus law, health law, hospital accreditation